Tradisi Islam Pesisir: Ritual Ngumbai Lawok Di Kabupaten Pesisir Barat Provinsi Lampung - Ruslan, Idrus; Wakhid, Ali Abdul (AL-ADYAN, 2019)
The people of Pesisir Barat Regency have local wisdom which, if understood, developed and managed properly, can contribute to regional development, especially in terms of tourism. Local wisdom is the ritual of tassel lawok. An interest in the Ngumbai Lawok ritual is an activity as an expression of gratitude for the fishing communities of Lampung Coastal to God for the favors they received while earning a living at sea. This text belongs to the type of field study while the nature of this writing is descriptive. This study aims to explain the Islamic tradition of Coastal namely the Ngumbai lawok ritual that comes from the ancestors needs to be enshrined. The process of implementing Ngumbai lawok fishing community in Pesisir Barat Regency is through three stages namely preparation, implementation and evaluation. The implementation of the Ngumbai Lawok ritual activities carried out in Pesisir Barat Regency does not yet have a significant contribution in the field of tourism. That is because the implementation of the Ngumbai Lawok ritual is still carried out traditionally and only relies on funds from the community (swadana) and has not been fully supported by the Regional Government of Pesisir Barat Regency.